Pembentukan Karakter Siswa Melalui Pembelajaran Pendidikan Agama Islam di SMP Negeri 1 Kaubun - Safitri Safitri; Sa’baniah Sa’baniah; Eko Nursalim (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The study describes the implementation of PAI learning in student character formation, the efforts made by PAI teachers in the formation of student character and the Supporting Factor as well as the Inhibitory Factor in the Formation of Student Character in the State 1 Kaubun. The study uses a qualitative approach. Collection method with observations, interviews, and documentation. The results of this study are: 1). Implementation of PAI learning in character formation for Students Based on PAI teacher creativity in delivering material, teacher compatibility as an example for his pupils as well as the habits instilled by the teacher to his pupil to do positive things. 2). The efforts made in building the character of the students are to create a program of sholat dzuhur jamaah to form a religious character and mandate the extracurricular pramuka as well as to emphasize the order of coming to school in time to form the character discipline and responsibility. 3). Supportive factors include external factors such as PAI teacher creativity and support from the school as well as internal character factors within the individual. And inhibiting factors in the effort to form the student's character include differences in the character of each student and family and environmental factors.